PENGARUH PENAMBAHAN UREA, KOMPOS CAIR, DAN CAMPURAN KOMPOS DENGAN GULA TERHADAP KANDUNGAN BOD DAN COD PADA PENGOLAHAN AIR LIMBAH PENCELUPAN - BUDIARSA SUYASA, I W.; DWIJANI, WAHYU (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 1)
Seed of Mikroorganisme from river mud sediment that sampling of Tebe counted ± 10 gr. Phase of seeding with capasity of 3 litre (sediment) of Tebe, was counted by 3 gr, NPK = 2,5 gr, Mgso4.7H2O = 0,2 gr, and aquades until border. Aerasi is conducted by using given aerator into seed place. Growth of microorganism was measured of each every 2 day during one week with measuring value of biomass till reach price 2000 mg / L. After seed process, into treatment place aeraeration of process of seeding domestic waste water and each counted 500 mL. Variation of nutrient treatment (NPK) respectely 0,25 gr, 0,50 gr, 0,75 gr and 1.00 gr while control without addition of nutrient. Process is measured by value of pH, COD on 1, 3, 5, and 7 day. Result of research show that Sediment River of Tebe have potency as active mud. This matter is showed with growth of biomass of microbe till reach number 3.610 mg / L. Addition variation of NPK at treat of domestic waste have an effect on very real to value of COD. Best Result with value of COD lowest that is 38,096 mg / L with its effectiveness to 91,11% at addition of NPK counted 0,5 gr.
Keywords: active mud, seeding, domestic waste